Problem-Based School Principal Competency Improvement Training: Pelatihan Peningkatan Kompetensi Kepala Sekolah Berbasis Masalah - Kristiawan*, Nana; Ramadhan, Putri Utami; Huda, Muhammad Nurul; Chahyati, Siti; Ramadhina, Zahra (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
The Problem-Based Principal Training activity aims to improve the competence of principals. This training is a solution to the minimal qualifications of prospective principals in the Mitra Grogol Petamburan environment by involving 25 participants. The training method consists of preparation, implementation, evaluation and reflection and follow-up. The results of the training evaluation showed an increase in the understanding of participants in the "Good" category from 25% to 75%, a decrease in participants in the "sufficient" category from 62.5% to 18.75%. The principal competency program contributes to improving the quality of educational leadership and opens up opportunities for further training with a data-based and reflection-based approach to support educational transformation. Thus, this training has succeeded in preparing prospective principals to face the challenges of educational leadership.